Pesticide residues risk assessment and quality evaluation of four characteristic fruits in Zhejiang Province, China - Liu, Yuhong; Bei, Ke; Zheng, Weiran; Yu, Guoguang; Sun, Caixia (Frontiers in Environmental Science, 2023)
Miaoxi yellow peach, lanxi loquat, qingyuan sweet spring tangelo and haining pear are characteristic fruits in Zhejiang Province, China. This study investigated the levels of pesticides in these fruits in Zhengjiang Province, China, along with the associated risk of dietary exposure for consumer. In total, 25 pesticides were detected in the 68 samples. The pesticide detection rate of the samples was 95.59%, and the level of prochloraz in a pear sample was found to be higher than the maximum residue limit (MRL) in China. Overall, the pesticide residues were very low, and residue levels ranged from 0.001 to 1.06 mg/kg, of which 80.88% simultaneously occurred with 2–8 mixed residues. Acetamiprid (54.55%), carbendazim (64.71%), prochloraz (94.74%) and pyraclostrobin (85.71%) had the highest detection rate in the four fruits, respectively. A risk assessment of human exposure to pesticides via the intake of the four fruit types was performed, and the chronic intake risk (HQc) and acute intake risk (HQa) of a single pesticide and the hazard index (HI) of the mixture of pesticides for adults and children from the four fruit types were found to be less than 1, the exposure assessment showed that the levels of pesticides in the four fruit types were safe for human consumption. In addition, the quality of the four fruit types was analyzed and found to be not stable enough. We suggest strengthening standardized planting and management technology to improve product quality and safety, in particular, cultivators should use pesticides reasonably and control the pre-harvest interval (PHI) in order to better protect consumer health.